Bimetal-organic frameworks/polymer core-shell nanofibers derived heteroatom-doped carbon materials as electrocatalysts for oxygen reduction reaction. (April 2017) - Niu, Qijian; Guo, Junxia; Chen, Binling; Nie, Jun; Guo, Xindong; Ma, Guiping
Abstract: In this work, Zn-Co-ZIF-n(shell)/PAN(core) nanofibers were well-designed and prepared through bimetal zeolitic imidazolate frameworks (ZIFs) grown on the surface of 2-Methylimidazole/Polyacrylonitrile (MIM/PAN) electrospun nanofibers. After carbonization of Zn-Co-ZIF-n/PAN nanofibers (n was the molar ratio of Zn/Co before carbonization), the core layer was converted to nitrogen-doped carbon nanofibers (NCNFs) and the shell layer was converted to Zn/Co bimetal nanoparticles coated with graphitic carbon layer (Zn/Co@C). It was found that Zn/Co@C-NCNFs are featured with hierarchical network structure and high surface area. Further doped by nitrogen species and embedded by Zn/Co bimetal nanoparticles, it exhibited excellent electrocatalytic performance for oxygen reduction reaction (ORR), better than the reference samples. By further investigating the electrocatalytic performance, the optimized sample Zn/Co@C-NCNFs (0.50) derived from Zn-Co-ZIF-0.50/PAN at 800 °C carbonization exhibited excellent electrocatalytic activity (the onset and half-wave potentials were −0.099 V and −0.20 V vs. Ag/AgCl, respectively and nearly four electron selectivity (3.69)). Moreover, its methanol tolerance and duration stability was better than that of the commercial 20 wt% Pt/C. It provides an effective strategy to design non-precious metal electrocatalysts from the Zn-Co-ZIF-n/PAN nanofibers or other MOFs/polymer nanofibers for ORR in fuel cells. Graphical abstract: The preparation process included three steps: Firstly, MIM/PAN nanofibers were prepared by electrospinning; Secondly, the nucleation and growth of Zn-Co-ZIF-n produced along the nanofiber surfaces; Lastly, Zn/Co@C-NCNFs were prepared by carbonization of Zn-Co-ZIF-n/PAN nanofibers. The colour of nanofiber film changed from white to purple, and finally became black in the preparation process.